Effectiveness of ICT-Based Intelligent System Using Cloud Computing for Research Programme During Covid-19 Pandemic - V. Vamsi Krishna, G. Gopinath (International Journal of Intelligent Systems and Applications in Engineering, 2023)
ICT-based education system refers to the education system which is based on “Information and Communication Technologies”. The use of ICT in the education system is very effective and efficient to enhance the engagement of the students towards their learning. The use of modern technology in the education system helps to enhance the productivity of the students. Therefore, the usage of technology in the education system of India is increasing day by day. There are several services of ICT-based education systems and among them cloud computing is one of the most important services for developing education systems. Thereafter cloud computing is a networking and technology-based process which help students to learn together. During the covid-19 pandemic situation the Government of India has declared a certain stoppage of the education system in the country and people had to maintain social isolation at the time. Moreover, the use of ICT-based education systems and cloud computing processes help the students to continue their education during the pandemic. Thus, the usage of cloud computing processes and ICT in the education system has mostly increased during the pandemic. Therefore, the purpose of this specific research article is to analyse the effectiveness of ICT-based education systems using cloud computing for research programs during the pandemic situation in India. The concept of ICT-based education system and cloud computing is analysed in this specific research article properly. Apart from that the usage of ICT based education system and soft computing for research programs is also analysed please research study. There are different types of cloud computing services and its impact on the education system is also different. Therefore, all the cloud computing services analysed below in this research article appropriately. The researcher has adopted several methods and techniques to gain more knowledge and information about ICT-based education systems and cloud computing. Thereafter, the researcher has adopted the primary techniques for gathering data and uses the quantitative method to analyse all the collected data in this research article properly. Thus, the impact of pandemic and cloud computing on the education system is analysed in the research article.